# Verify if lnx-2(x-1)/(x+1)>0.

### 1 Answer | Add Yours

We'll note the given expression:

f(x) = lnx-2(x-1)/(x+1)

We'll have to demonstrate that f(x)>0.

To prove that a function is increasing, we'll have to prove that the first derivative of the function is positive.

We'll calculate the first derivative:

f'(x) = [lnx-2(x-1)/(x+1)]'

The ratio from the expression of the function will be differentiated using the quotient rule.

f'(x) = (1/x)-{[2(x-1)'*(x+1)-2(x-1)*(x+1)']/(x+1)^2}

f'(x) = (1/x)-(2x+2-2x+2)/(x+1)^2

f'(x) = (1/x)-(4)/(x+1)^2

f'(x) = [(x+1)^2-4x]/x*(x+1)^2

f'(x) = (x^2+2x+1-4x)/x*(x+1)^2

f'(x) = (x^2-2x+1)/x*(x+1)^2

f'(x) = (x-1)^2/x*(x+1)^2

**We notice that for any x>1, (x-1)^2>0 and x*(x+1)^2>0, so f(x)>0.**

**f(x) = lnx-2(x-1)/(x+1)**

**lnx-2(x-1)/(x+1) > 0 q.e.d.**